MAKSI for ICT-based accounting learning at vocational high schools - Vivi Pratiwi; Moh. Danang Bahtiar; Han Tantri Hardini (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This study aims to produce ICT-based learning media for Vocational High Schools (VHS) in the form of ICT-based accounting multimedia application, named